2014
DOI: 10.1016/j.virusres.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of intracellular pathways of engineered baculovirus in mammalian cells

Abstract: Baculoviruses are a promising gene delivery vector. They have the ability to express large transgenes in mammalian cells without displaying pathogenicity in humans; however, little is known about their transduction mechanisms in target cells. In this study, we use colocalization and live-cell imaging studies to elucidate the internalization and intracellular trafficking pathways of baculoviruses through direct visualization of VP39-GFP-labeled viral particles and various endocytic structures within target cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…2). This is consistent with a previous report indicating that perturbation of the function of the EE by a dominant-negative Rab5 mutant, but not of the LE by that of Rab7, significantly reduced AcMNPV transduction in HeLa cells (30).…”
Section: Discussionsupporting
confidence: 93%
“…2). This is consistent with a previous report indicating that perturbation of the function of the EE by a dominant-negative Rab5 mutant, but not of the LE by that of Rab7, significantly reduced AcMNPV transduction in HeLa cells (30).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the assumption that the pH of early endosomes is 6.0 to 6.5 is probably not applicable for endosomes in insect host Sf9 cells. Our study is further confirmed by the findings that AcMNPV nucleocapsid release in mammalian cells occurs also primarily in early endosomes but not late endosomes (31,75,76).…”
Section: Discussionsupporting
confidence: 87%
“…The constructs are normally used to visualize EEs (RAB5A) or LEs (RAB7). The expression of the proteins encoded by the plasmid requires the transport of baculovirus particles to the LE, 28 plasmid release and import into the nucleus. We compared the efficiency of BacMam 2.0 technology in HD and PT1 fibroblasts.…”
Section: Nfkb Does Not Translocate To the Nucleus In Response To Cpgmentioning
confidence: 99%